Características de qualidade do mel de abelha (Apis mellífera L.) da mesorregião Oeste Potiguar do estado do Rio Grande do Norte, Brasil - Mesquita, Luciene Xavier de (2010)
It is the honey produced by Apis mellifera L. Mesoregion Potiguar West - RN -Brazil meet specifications certain laws. We analyzed 73 samples of honey determining the physical and chemical parameters, qualitative tests (Fiehe, diastatic ferment and Lugol), sensory and microbiological samples were honey collected in the homes of around 500 ml per beekeeper and analyzed 48 collected after each hour. The collection period was from March 2008 to September 2009. The results were the predominant color with 36% of amber light, moisture (20.16% ± 3.44%), water activity (0.620 ± 0.027%), solid (0.329 ± 0.311%), ash (0.146 ± 0.086%), density (1.402 g.cm-1 ± 0.034), pH (3.39 ± 0.49), acidity (38.07 mEq / kg ± 16.45), sugars (63.24 ± 10.25%), sucrose (5.674% ± 1.02), HMF (10.94 mg / kg ± 4.91), Lund (0621 +0.257%) and conductivity (0.356 mS / cm ± 0.125), negative results for the qualitative tests, 18 samples with yeast and mold growth and 15 samples with coliform and total coliforms. The HMF values, acidity, color, ash were in agreement with the regulations of BRAZIL (2000), Codex (2001) and MERCOSUL (GMC 89/99) and conductivity, sugars according to the Codex (2001), 18 samples were values greater than 100 CFU / g for molds and yeasts and 15 had values above <3NMP / g opposing MERCOSUR (GMC 89/99). The characteristics of honey samples produced that do not conform with the standards indicate the need for a revision of these standards and who have the honey microbial growth suggest the application of best practices for beekeeping.